Tolerance of Ambiguity (TOA) and EFL Students Anxiety: Writing Mini Research Report at FKIP Universitas HKBP Nemmensen Pematangsiantar - Dumaris Elserida Silalahi; Asima Rohana Sinaga; Rick Hunter Simanungkalit; Lydia Purba; Josua Silalahi (PIJAR: Jurnal Pendidikan dan Pengajaran, 2026)
This research aims to investigate the role of tolerance of ambiguity (ToA) and EFL learners’ anxiety sources in writing. The object of this research is the learners’ writing on composing mini research as the project of the lecture. The valuable is indicated by considering the criteria of academic writing. The researcher’s observation indicates that the learners’ writing is not optimal caused by the anxiety. The writing anxiety hinder the learners to achieve the learning objective. Anxiety has to be avoid in order to treat the learners to be active and enjoy in English learning. The individual ability in hindering anxiety is the optimizing of ToA which make the ambiguous stimuli to be interpreted based on the contextual meaning. More over anxiety can be hinder by interpretation of information as the cognitive style refers to ToA. Learners’ writing anxiety will be investigated by interview and questionnaires of foreign language classroom anxiety scale (FLCAS). The data will be taken from the learners of one group investigation as the research subject at seminar on ELT class. Anxiety is psychological discomfort, which makes the learners to be lack of confidence in writing. It affects the learning objective achievement, so it is needed to be to be considered seriously. This condition encourages the researcher to investigate and minimize anxiety in writing. The anxiety in English writing is possible happened as foreign language with new various aspect learnt. The learners’ anxiety in writing mini research will be use as evaluation in teaching and learning English. The research result will be used to evaluate and improve the teaching and learning process at English department of FKIP Universitas HKBP Nommensen Pematangsiantar. The result of this research is hoped to be valuable refers to the learning anxiety avoiding. The result of this research will composing in an article and publish in journal sinta 4 indexed reputation